ARE BIRDS MODERN-DAY DINOSAURS? : DISCOVER THE SCIENCE BEHIND ORNITHOLOGY (or-nih-THO-luh-jee) - Watson, Olivia; Abatzoglu, Valeria; Thornton, Holly; Burdett, Millie (Truro, Cornwall, England : Beetle Books, an imprint of Hungry Tomato Ltd., 2024)
"Dinosaurs ruled the Earth for millions of years and are now extinct, but could some have survived and are now the birds we see today? Check out: if we still walk with dinosaurs, the prehistoric bird big enough to attack a saber-toothed tiger, the amazing ways that birds help our planet, and so much more! Reading the incredible stories behind ornithology, kids will be eager to find out the answer to are birds modern-day dinosaurs? Beautifully bound with stunning illustrations, this unique and collectable series will start a lifelong interest in science for curious kids. QR codes link to the Big Questions Answered website for comprehensive, free teacher resources and a fun kids' pack"--Amazon.
Keywords: Ornithology -- Juvenile literature; Birds -- Juvenile literature; Illustrated works